GENERATION OF LIGHT THROUGH PLASMA USING RADIO FREQUENCY SOURCE IN DISUSED FLUORESCENT TUBE - M, Adekanmbi; E.O, Abumere; J.A, Amusan (International Journal of Research -GRANTHAALAYAH, 2018)
Light has been generated through Plasma using radio frequency source in 4Ft 40W disused fluorescent tube. As against the thermionic and incandescence source of running a fluorescent tube which is actually difficult to get started due to the resistance of the gases enclosed inside, a Radio Frequency signal of 30MHz generated using a designed Hartley Oscillator is employed. The power of the signal generated is amplified from 231mW to 197.8W using a modeled inverter. The coupled Hartley oscillator and the inverter form an ionizing circuit. The gases inside fluorescent tube consist of mercury Vapor, argon, krypton or Neon. When sufficient energy is supplied to these gases, by the ionizing circuit, ionization and excitation takes place which makes otherwise neutral gases, to change state to a cloud of ionized gas called Plasma. When excited electrons in the gases return to the ground state they lose energy in packets called Photon. This Photon is ultraviolet light which is not visible to the human eye but when it strikes the walls of the tube coated with Phosphor it glows whereby light is generated. The high electric field Radio frequency circuit designed has generated light in a fluorescent tube without the use of starter and ballast. It has also generated light in otherwise “dead” or disused fluorescent bulbs.